2003
DOI: 10.1016/s0005-2728(03)00024-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of biphasic forward electron transfer from the phylloquinone(s) A1 in photosystem I: only the slower phase is activated

Abstract: The temperature dependence of the biphasic electron transfer (ET) from the secondary acceptor A1 (phylloquinone) to iron-sulfur cluster F(X) was investigated by flash absorption spectroscopy in photosystem I (PS I) isolated from Synechocystis sp. PCC 6803. While the slower phase (tau=340 ns at 295 K) slowed upon cooling according to an activation energy of 110 meV, the time constant of the faster phase (tau=11 ns at 295 K) was virtually independent of temperature. Following a suggestion in the literature that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
82
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 15 publications
14
82
0
Order By: Relevance
“…Although the focus of this paper was on the reduction of P 700 + by plastocyanin in vivo, we were able to estimate the activation energy of forward ET from PhQ A and PhQ B to be 107-130 meV and 8-47 meV, respectively. These agree reasonably well with the estimates of 65-110 meV and 7-15 meV, obtained in work with purified cyanobacterial PS1 in vitro using a more extensive temperature range (Agalarov and Brettel, 2003).…”
Section: Temperature Dependence Of Et Reactions In Ps1 In Vivosupporting
confidence: 89%
“…Although the focus of this paper was on the reduction of P 700 + by plastocyanin in vivo, we were able to estimate the activation energy of forward ET from PhQ A and PhQ B to be 107-130 meV and 8-47 meV, respectively. These agree reasonably well with the estimates of 65-110 meV and 7-15 meV, obtained in work with purified cyanobacterial PS1 in vitro using a more extensive temperature range (Agalarov and Brettel, 2003).…”
Section: Temperature Dependence Of Et Reactions In Ps1 In Vivosupporting
confidence: 89%
“…However, this is not surprising in light of a recent optical study on PS I from Synechocystis sp. PCC 6803 that showed that the rate of the fast phase was virtually independent of temperature and that its relative amplitude decreased from ϳ28% at room temperature to ϳ20% at 260 K (35). Three other observations at 260 K are surprising, however.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the observation of a change in the high-field region along with the appearance of a higher frequency shoulder in the dipolar spectrum (this work) may be explained by a partial block in electron transfer through the A-branch due to the change in the ligand to A 0A and the uncovering of the relatively small amount of electron transfer through the B-branch. It remains to be explained how the otherwise fast electron transfer through the B-side cofactors can be observed within the limited EPR time window [20] even at 100 K, given that there is little or no activation energy associated with this electron transfer step [28]. Perhaps, because Asn can potentially form an H-bond to the second C=O of the quinone, the position of the A-branch quinone could have moved in some of the PS I complexes to a position closer to P 700 Á ?…”
Section: Discussionmentioning
confidence: 99%